Peran Psikologi Dalam Pencegahan Cedera Pada Atlet - Nimrot Manalu; Miftahul Ihsan; Zulkifli Sirait; Ruth Saragih; Abdul Hapit; Ruben Simanjuntak; Stevany Siregar; Ricardo Malau; Andes Martua (Jurnal Sains Farmasi Dan Kesehatan, 2025)
Injury is one of the biggest challenges for athletes, which not only affects the physical but also the psychological aspects. This study aims to analyze how psychological factors, such as stress management, focus, and motivation, play a role in preventing injuries in athletes. The research method used is a quantitative study with a survey approach to 150 athletes from various sports. The results of the study showed that psychological factors have a significant relationship with the risk of injury, where athletes with high levels of anxiety are more susceptible to injury compared to those with good stress management. Therefore, the application of sports psychology techniques, such as relaxation, visualization, and mindfulness, can be an effective strategy in preventing injuries in athletes.